RNA Interference Targeting Snail Inhibits the Transforming Growth Factor β2-Induced Epithelial-Mesenchymal Transition in Human Lens Epithelial Cells - Ping Li; Jiaona Jing; Jianyan Hu; Tiejun Li; Yuncheng Sun; Huaijin Guan (Journal of Ophthalmology)
Epithelial-msenchymal transition (EMT) contributes to posterior capsule opacification (PCO) type of cataract. Transcription factors Snail is a key trigger of EMT activated by transforming growth factor β (TGFβ). This study was done to investigate the effect of Snail targeting siRNA on TGFβ2-induced EMT in human lens epithelial cells. TGFβ2 treatment of cultured human epithelial cell line (HLEB3) upregulated the expression of Snail and the EMT relevant molecules such as vimentin and α-SMA but downregulated the expression of keratin and E-cadherin. After the stimulation of TGFβ2, the HLEB3 cells became fibroblast-like in morphology, and the junctions of cell-cell disappeared. TGFβ2 treatment also enhanced migration ability of HLEB3 cells. TGFβ2-induced Snail expression and EMT were significantly inhibited by Snail siRNA. By analyzing the response characteristics of HLEB3 in TGFβ2-induced EMT model with/without Snail-specific siRNA, we concluded that Snail is an element in the EMT of HLEB3 cells induced by TGFβ2. Snail siRNA targeting can block the induced EMT and therefore has the potential to suppress the development of PCO.